Serum levels of MMP-11 correlate with clinical outcome in Chinese patients with advanced gastric adenocarcinoma - Liu Jin-Wei; Dai Hong; Yan Dong (BMC Cancer, 2011)
Abstract Background The aim of the present study was to investigate the association between serum levels of matrix metalloproteinase 11 (MMP-11) and responses to front-line chemotherapy and prognosis in advanced unresectable gastric adenocarcinoma. Methods Clinical data concerning 86 patients with advanced gastric adenocarcinoma (stages III c to IV), treated in Beijing Chao-Yang Hospital from 2005 to 2009, were reviewed retrospectively. Adenocarcinoma was confirmed by pathology and patients received 5-fluorouracil-based front-line combination chemotherapy with third generation chemotherapeutic agents including paclitaxel, docetaxel and oxaliplatin. The regimen was repeated every two to three weeks, and the first evaluation was carried out after three cycles. The median cycle of chemotherapy was 6 (ranging from three to twelve cycles). Serum MMP-11 protein from the 86 patients was examined using enzyme-linked-immunosorbent-assay (ELISA) prior to chemotherapy and after three cycles of chemotherapy. Serum samples from healthy individuals were used as controls. Results The response rate (RR, complete response plus partial response) to chemotherapy in the 86 patients was 44.2% (38/86). The median TTP (time to progression) and overall survival (OS) in patients who responded to chemotherapy were 6.0 and 10.0 months, respectively. The response rate to chemotherapy in patients with high levels of serum MMP-11 (42.9%; 9/21) was similar to that in patients with low levels (44.6%; 29/65) (P = 0.935). Patients with low serum levels of MMP-11 had a higher median survival time and 1-year survival rate than those with high levels (11 months vs. 8 months, 50.2% vs. 21.7%, P = 0.017), although the TTP was comparable in all patients, irrespective of serum MMP-11 level (P = 0.178). Serum MMP-11 levels were correlated with lymph node metastasis (P = 0.006). Cox multivariate regression analysis demonstrated that the serum level of MMP-11 was an independent prognostic factor for patients presenting with advanced gastric carcinoma. Conclusions Serum levels of MMP-11 in Chinese patients with advanced gastric carcinoma were not associated with the response to front-line chemotherapy, but could play an important role in lymph node metastasis and prognosis.